A design method for active high–CMRR fully–differential circuits. (16th April 2013) - Spinelli, Enrique Mario; Hornero, Gemma; Casas, Oscar; Haberman, Marcelo
A simple method for designing instrumentation fully–differential (FD) circuits based on standard single–ended (SE) operational amplifiers (OAs) is presented. It departs from a SE prototype that verifies the desired differential–mode transfer function, thereby leading to FD versions of the circuit. These circuits have a high common mode rejection ratio (CMRR), independent of component imbalances, and a unity common–mode gain. The proposed method does not allow the design of common–mode response, but it does verify common–mode stability, thus ensuring stable FD circuits. It is intended for instrumentation applications in which high CMRRs are required. The proposed approach makes it possible to design and implement inverter and non–inverter topologies as well. Design examples and experimental data are presented. Using general–purpose OAs and 5%–tolerance components, the CMRR of these circuits easily exceeds 90 to 100 dB.